Increase of Stroke Incidence in Young Adults in a Middle-Income Country: A 10-Year Population-Based Study. Issue 11 (November 2017) - Cabral, Norberto Luiz; Freire, Aracélli Tavares; Conforto, Adriana Bastos; dos Santos, Nayara; Reis, Felipe Ibiapina; Nagel, Vivian; Guesser, Vanessa V.; Safanelli, Juliana; Longo, Alexandre L.
Abstract : Background and Purpose—: The incidence of stroke is on the rise in young adults in high-income countries. However, there is a gap of knowledge about trends in stroke incidence in young adults from low- and middle-income countries. We aimed to measure trends in incidence of ischemic stroke (IS) and intracerebral hemorrhage (IH) in young people from 2005 to 2015 in Joinville, Brazil. Methods—: We retrospectively ascertained all first-ever IS subtypes and IH that occurred in Joinville in the periods of 2005 to 2006, 2010 to 2011, and 2014 to 2015. Poisson regression was used to calculate incidence rate ratios of all strokes, IS, and IH. We also compared the prevalence of risk factors and extension of diagnostic work-up across the 3 periods. Results—: For 10 years, we registered 2483 patients (7.5% aged <45 years). From 2005 to 2006 to 2014 to 2015, overall stroke incidence significantly increased by 62% (incidence rate ratios, 1.62; 95% confidence interval, 1.10–2.40) in subjects <45 years and by 29% in those <55 years (incidence rate ratios, 1.29; 95% confidence interval, 1.04–1.60). Incidence of IS increased by 66% (incidence rate ratios, 1.66; 95% confidence interval, 1.09–2.54), but there was no significant change in incidence of IH in subjects <45 years. Smoking rates decreased by 71% (odds ratio, 0.29; 95% confidence interval, 0.12–0.68). Conclusions—: Stroke incidence is rising in young adults in Joinville, Brazil, because of increase in rates of ischemic but not hemorrhagic strokes. We urgently need better policies of cardiovascular prevention in the young. Abstract : Supplemental Digital Content is available in the text.